Concomitant occurrence of infected cemento-osseous dysplasia and radicular cyst in young Indian female: An unusual case report - Pasha Zameer; A N Sulabha; Sameer Choudhari (Wolters Kluwer Medknow Publications, 2013)
Cemento-osseous dysplasia is a non-neoplastic process usually confined to the tooth bearing areas of jaws or edentulous alveolar process. Cemento-osseous dysplasias are categorized into three types on basis of the clinical and radiographic features: Periapical, focal and florid. Focal cemento-osseous dysplasia is benign fibrous osseous condition that can be seen in dentulous and edentulous patient. The lesion is detected only on radiographic examination with variation comprising a combination of radiolucent and radiopaque pattern. It is asymptomatic and needs no treatment. We report an unusual case of concomitant occurrence of infected focal cemento-osseous dysplasia in mandible with atypical clinical presentation of two sinus openings and a radicular cyst in maxilla.